Evaluating the impact of a medical school cohort sexual health course on knowledge, counseling skills and sexual attitude change - Michael W. Ross; Carey Roth Bayer; Alan Shindel; Eli Coleman (BMC Medical Education, 2021)
Abstract Background Sexual health is generally considered an integral part of medical and allied healthcare professional training. However, many medical schools do not offer this as a mandatory curriculum, or minimize it. Sexual health as an academic area was introduced in the 1970s, but there have been few cohort evaluations of its impact. This was limited by the availability of few psychometric scales for evaluation. We evaluated the full, mandatory, sexual health course in year 1 medicine at a large state university in the Midwest US, including the course with lectures; panels and tutorials; a video app to give students feedback on their sexual history taking skills; and a 3-station sexual history OSCE at the end of the course. Results Seventy-four medical students (43% of the course cohort) volunteered, for an incentive, to complete evaluation materials pre- and post-course. We used the Sexual Health Education for Professionals Scale (SHEPS), designed and with appropriate psychometric standardization for such evaluation. The SHEPS data covers 7-point Likert scale ratings of 37 patient situations, asking first how well the student could communicate with such a patient, and on the second part how much knowledge they have to care for such a patient. The third subscale examines personal sexual attitudes and beliefs. Data indicated that the matched pretest-posttest ratings for skills and knowledge were all statistically significant and with very large effect sizes. Few of the attitude subscale items were significant and if so, had small effect sizes. Sexual attitudes and beliefs may be well-formed before entry into medical school, and sexual health teaching and learning has minimal effect on sexual attitudes in this US sample. However, using the 3 sexuality OSCE cases scores as outcomes, two of the 26 attitude-belief items predicted > 24% of the variance. Conclusions The sexual health course produced major changes in Communications with patients sexual health skills and Knowledge of sexual health, but little change in personal Attitudes about sexuality. These data suggest that personal attitude change is not essential for teaching US medical students to learn about sexual health and sexual function and dysfunction, and comfortably take a comprehensive sexual history.